International law in a multipolar world - International Law Association. Conference (2009 : Hull, England); Happold, Matthew; International Law Association. British Branch (Milton Park, Abingdon, Oxon : Routledge, 2011)
'Since the creation of the United Nations in 1945, international law has sought to configure itself as a universal system. And yet, despite the best efforts of international institutions, scholars and others to assert the universal application of international law, its relevance and applicability has been influenced, if not directed, by political power. Over the past decade, discourse has tended to focus on the implications for international law of a unipolar world, characterised by US hegemony. However, that the international system may now be experiencing a tendency towards multipolarity, with various sites of power able to exert a telling influence on international relations and international law. Recent events such as Russia's excursion into Georgia, the breakdown of the Doha round of trade negotiations, the USA's questionable actions in the War on Terror, the prominence of emerging nuclear powers, China's assertions of its own interests on a global scale, and the rise of regional trading blocs, all pose significant questions for international law and the international legal order. International Law in a Multipolar World features contributions from a range of contributors including Nigel White, Michael Schmitt, Richard Burchill, Alexander Orakhelashvili and Christian Pippan, addressing some of the questions that multipolarity poses for the international legal system. The contributions to the volume explore issues including the use of force, governance, sovereign equality, regionalism and the relevance of the United Nations in a multipolar world, considering the overarching theme of the relationship between power and law'--
'Since the creation of the United Nations in 1945, international law has sought to configure itself as a universal system. Yet, despite the best efforts of international institutions, scholars and others to assert the universal application of international law, its relevance and applicability has been influenced, if not directed, by political power. At present, the international system appears to be moving towards multipolarity, with various sites of power competing to exert influence in the world today. The ascent of China and India and the'decline of the West' all pose challenges for international law and institutions. With contributors from a variety of countries providing perspectives from the disciplines of international law and international relations theory, International Law in a Multipolar World addresses the implications that multipolarity poses for the international legal system. The book features contributions addressing some of the questions multipolarity poses for the international legal system. The contributions to this volume from a range of contributors including Nigel White, Michael Schmitt, Richard Burchill, Alexander Orakhelashvili and Christian Pippan, explore issues such as the use of force, governance, sovereign equality, regionalism and the relevance of the United Nations in a multipolar world, while considering the overarching theme of the relationship between power and law. International Law in a Multipolar World is of particular interest to academics and students of public international law, international relations theory and international politics'--
International law in a multipolar world: introduction / Matthew Happold -- The Security Council, the security imperative, and international law / Nigel White --Ascertaining inchoate threats to international peace and security / Isobel Roele -- Nuclear non-proliferation and the UN Security Council in a multipolar world / Daniel Joyner -- Using force in international affairs: the role of international law in contemporary international politics / Dominika Varc -- Russia and competing spheres of influence: the case of Georgia, Abkhazia and South Ossetia / James Summers -- Hegemony, multipolarity and the system of international law / Alexander Orakhelashvili -- Orthodox generalists versus political activists in international legal scholarship / J$1'Xr(Bg Kammerhofer -- Basic rights and global justice: the problem of international coercion / Silviya Lechner -- The duality of the legitimacy of global actors in the international legal order / Jean d'Aspremont and Eric de Brabandere -- Democracy as a global norm: has it finally emerged? / Christian Pippan -- International law and East Asia's regional order: the strengthening of a fundamental institution / Pablo Pareja Alcaraz -- Post-soviet states and international law in a multipolar world / Rima Tkatova -- Universality, the UN and the organisation of the Islamic conference: single, complementary or competing legal orders? / Katja Samuel -- The development of self-contained regimes as an obstacle to un global governance / Carmen Draghici -- The relationship between community law and international law after Kadi: did the ECJ slam the door on effective multilateralism? / Aurel Sari.s
'[P]apers presented at the 2009 spring conference of the British Branch of the International Law Association, hosted by the University of Hull Law School in April 2009.' -- Introduction.
Keywords: International law -- Congresses; International organization -- Congresses